Experience of Nurses in Providing Rehabilitation Therapy Programs for Adolescents Using Narcotics, Psychotropic and Other Addictive Substances (NAPZA) - Puguh Raharjo; K Kumboyono; Yati Sri Hayati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Nurses who handle drug cases in adolescents need to focus on adjusting the social, emotional and physical aspects of the family through intervention at a rehabilitation therapy centre. This study aims to explore the experience of nurses in providing rehabilitation therapy programs to adolescent drug users. The research design uses qualitative methods with an interpretive phenomenological approach. In-depth interviews were conducted with 6 nurses at the Hayunanto Medical Center Drug Rehabilitation Center. This study resulted in 10 themes, including 1)feeling concerned about adolescent drug users, 2) being happy when successfully curing patients, 3) being frustrated seeing patients relapse and being rehabilitated again, 4) being challenged to devote themselves, 5)the key to successful treatment is to do more assessment and communication, 6)use various approaches to overcome obstacles, 7)interaction still carried out through outpatient and home visits, 8)difficulties in understanding the holistic aspects of patients, 9)the need for involvement of various parties in overcoming drug abuse, 10)the need to increase interventions involving social media. The conclusion of this study is that the experience of nurses in providing therapy programs to adolescent patients with drugs causes various conditions felt by nurses, it is necessary to involve several parties as supporting factors for achieving therapeutic programs for adolescent NAPZA users. Abstrak: Perawat yang menangani kasus NAPZA pada remajaperluberfokus pada penyesuaian aspek sosial, emosi dan fisik pada keluarga melalui intervensi di pusat terapi rehabilitasi. Penelitian ini bertujuan untuk mengeksplorasi pengalaman perawat dalam memberikan program terapi rehabilitasi pada remaja pengguna NAPZA. Desain penelitian menggunakan metode kualitatif dengan pendekatan fenomenologi interpretif. Wawancara mendalam dilakukan pada 6 perawat di Pusat Rehabilitasi Narkoba Hayunanto Medical Center. Penelitian ini menghasilkan 10 tema yaitu 1)merasa prihatin menghadapi remaja pengguna NAPZA, 2)bahagia ketika berhasil menyembuhkan pasien,3) frustasi melihat pasien kambuh dan direhabilitasi kembali,3)tertantangmengabdikan diri,5)kunci keberhasilan perawatanadalah lebih banyak melakukan pengkajian dan komunikasi, 6)menggunakan berbagai pendekatan untuk mengatasi hambatan, 7)interaksi tetap dilakukan melalui rawat jalan dan home visit,8)kesulitanmemahami aspek holistik pasien,9)perlunya keterlibatan berbagai pihak dalam mengatasi penyalahgunaan NAPZA,10)perlunya meningkatkan intervensi yang melibatkan media sosial. Kesimpulan penelitian ini adalah pengalaman perawat dalam pemberian program terapi pada pasien remaja dengan NAPZA menimbulkan berbagai kondisi yang dirasakan perawat, perlu keterlibatan beberapa pihak sebagai faktor pendukung tercapainya program pemberian terapi pada remaja pengguna NAPZA.